Neuroprotective effects of Coriandrum sativum and its constituent, linalool: A review - Mahmoud Hosseini; Mohammad Hossein Boskabady; Mohammad Reza khazdair (Mashhad University of Medical Sciences, 2021)
Objective: Coriander (Coriandrum sativum L.) is an annual herb belonging to the Apiaceae (Umbellifera) family that is used as food additives traditionally. This plant is called "Geshniz" in Persian and is native to Mediterranean regions but it is currently cultivated in several countries. All parts of coriander are edible and have been traditionally used to treat different disorders, including digestive problems, flatulence, diarrhea, colic and other gastrointestinal diseases. Materials and Methods: The databases PubMed, Web of Science, Google Scholar and Scopus were considered. The search terms were "Coriandrum sativum" or "linalool" and "anti-anxiety", "sedative", "antioxidant effect", "anticonvulsant" and "neuroprotective effect". Results: Antioxidant, diuretic, cholesterol lowering, anxiolytic, sedative-hypnotic and anticonvulsant activities were reported for the seeds and leaves of the plant. Furthermore, linalool as the main component of coriander has different neuropharmacological effects, including anti-anxiety, sedative, anticonvulsant and anti-Alzheimer's disease activities. Conclusion: Various neuropharmacological effects of C. sativum and its component which have antioxidant and anti-inflammatory effects, have been summarized in the current review article.